The role of internal audit on the quality of financial reports - Majidah, Nurin; Falikhatun, Falikhatun (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to provide empirical evidence regarding the importance of the role of Internal Audit in the quality of financial statements reviewed from the Literature Study using 53 Sinta 2 journals and Scopus 4 indexed journals with a total of 57 journals. Here, we classify articles based on topics and this research uses the literature review method of the Sinta 2 journal and some from Scopus. The researcher reviewed research related to internal audits in Indonesia in Sinta and Scopus indexed journals., then a mapping approach (Charting the field) was carried out using a prism approach, matrix tables and previous research that strengthened this research. The results of the study found that the quality of financial statements was the most researched.  In addition, there is a research gap regarding the role of internal audit on the quality of financial statements as a proxy for Organizational Culture and Masculinity. It is evident that the results of previous studies are still inconsistent. Therefore, the researcher provides novelties that need to be reviewed regarding how Organizational Culture and Gender affect the quality of Financial Statements.